THE ALTERATION OF SOCIAL ISSUES OVER THE BEATLES' CAREER PERIODS:A Critical Discourse Analysis of the Beatles' Song Lyrics - Yuni Safitri, - (2012)
THE ALTERATION OF SOCIAL ISSUES OVER THE BEATLES' CAREER PERIODS: A Critical Discourse Analysis of the Beatles' Song Lyrics This study focuses on the alteration of social issues expressed in the Beatles' song lyrics over the three periods of their career as a band. The purpose of the study is to investigate the social issues that are presented and the ways the social issues are represented in the song lyrics. The study is qualitative research, which employs Fairclough's three dimensional framework of Critical Discourse Analysis (CDA) as the analytical framework. In addition, Systemic Functional Grammar proposed by M.A.K. Halliday is used as the tool for analysis, focusing on the Thematization (Macrostructure) and Transitivity (Microstructure) analysis. As the data, seven lyrics of the Beatles were selected purposely based on Heinonen's periodization of the Beatles' career. This study reaffirms Fairclough's theory that between discourse and social change in the society there is a dialectical relationship. It is proved by the results of the analysis which showed that from the early to the middle and to the late period of the Beatles' career, the social issues in the Beatles' song lyrics were shifted from the love relationship issue to the drugs abuse issue and finally to the political issue. This alteration is closely related to the social changes at that time.